Environmental barriers and correlations of self-rated driving confidence among older Malaysian drivers - Syed Abdul Rashid, Sharifah Norazizan; Yeoh, Sok Foon; Chan, Benjamin Yin Fah (Canadian Center of Science and Education, 2010)
As population age, it is becoming more important to identify the environmental aspects of driving among the older persons. This study aims to investigate the driving confidence and the influence of environmental barriers on driving among older Malaysian drivers. The cross-sectional data was obtained via face-to-face interview protocol. A total of 400 older adults aged 50 years and above were used in the quota sampling stratified by gender and age in the states of Perak and Selangor. Multiple Linear Regression analysis showed the ten predictor variables (gender, ethnicity, employment status, self-rated health status, driving ability, psychomotor ability, driving distance, weekly driving frequency, driving knowledge, perceived environmental barriers) which accounted for 32.1 percent of variance in driving confidence (F = 18.28, p < 0.05). Information about the determinants of driving confidence and environmental factors is significant providing insights for future road planning system and as input for driving training programs.